Bulgaria Financial Sector Assessment Program : Nonperforming Loans Reduction Strategy - International Monetary Fund; World Bank (World Bank, Washington, DC, 2017)
This Technical Note (TN) examines the current state of NPLs in Bulgaria and makes recommendations for a strategy to substantially reduce NPLs. These strategy recommendations were developed based on an assessment of the relevant regulatory and supervisory framework and bank practices, including relevant standards and practices for accounting treatments, early warning systems, NPL market development, and collateral valuation. The TN sets forth macroprudential approaches and other components of a sound strategy for NPL reduction, including improvements to loan loss provisioning, income recognition on NPLs, loan write-downs, early warning systems, collateral valuation, risk information for investors, and the NPL market. The NPL management process involves many stakeholders, and their mutual cooperation is important for success. The Bulgarian National Bank (BNB), in its capacity as bank supervisor and regulator and as macroprudential authority for banks, will be in the lead position on the implementation of key aspects of the NPL reduction strategy that can achieve progress in the near term. Broader policies to enhance NPL resolution entail other stakeholders, including the Ministry of Justice (MoJ) that would need to engage in the areas of insolvency and collateral enforcement regimes.